Elements, compounds & mixtures - Rees, Rod; Video Education Australia (Victoria : Video Education Australia, 1997)
This video ovorviews the distiction between elements, compund and mixtures.
Executive producer, David Brown ; script, Rod Rees
Presenter, Siobhan Gleeson
Keywords: Chemical elements; Chemistry, Inorganic